Research of the assortment and information support of medical products and cosmetics - I. Ya. Horodetska; О. R. Levytska; I. L. Chukhraу (Фармацевтичний журнал, 2022)
An urgent problem of the contemporary domestic pharmaceutical market is the availability of a large number of products and goods that are not registered as medicines in the prescribed manner, but declare in different ways the medicinal properties and uses for therapeutic purposes. Without unified and comprehensible information resources on such products, this function is partially performed by the site Compendium.onLine.